Effect of trace mineral (mineral capsule) supplementation on nutrient utilization and rumen fermentation pattern in Sahiwal cows (Bos indicus) - TIWARI, S P; JAIN, R K; MISHRA, U K; MISHRA, O P; PATEL, J R; RAJAGOPAL, S (The Indian Journal of Animal Sciences, 2013)
The effect of supplementation of trace minerals, viz. Cu, Co, Mn and Zn on the utilization of nutrients and rumen fermentation pattern was studied in 16 Sahiwal cows. They were divided at random into 2 groups of 8 animals each. All the animals were individually offered green berseem and para grass (Brachiaria mutiea) ad lib. and standard concentrate mixture 3 kg/day. An additional amount of 1 kg crushed maize grain/day per animal was offered in both the groups. Group 1 was kept as control while group 2 was supplemented with Cu, Co, Mn and Zn in the form of gelatinised capsule (3.34,0.442, 7.62 and 125.73 mg/day) respectively. The experiment lasted for 120 days. Digestion trial was conducted on 8 cows of 4 in each group. The intake of DCP and TDN in groups 1 and 2 were 0.913, 0.903 and 6.33, 5.58 kg/day which were statistically nonsignificant (P